2022
DOI: 10.14701/ahbps.21-124
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas-preserving limited duodenal resection: Minimizing morbidity without compromising oncological adequacy

Abstract: Backgrounds/Aims: Pancreaticoduodenectomy is the most common procedure for the management of duodenal pathologies. However, it is associated with substantial morbidity and a low risk of mortality. Pancreas-preserving limited duodenal resection (PPLDR) can be performed under specific scenarios. We share our experience with PPLDR and its outcome. Methods: We retrospectively analyzed a prospectively maintained database of patients undergoing limited duodenal resection in the form of wedge (sleeve) resection or se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Side-to-side duodenojejunostomy is a technically easier procedure, owing to wide stoma and sparing of mesenteric side. [ 12 ] Lastly, it was left to determine the oncological adequacy in terms of short- and long-term survival, recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Side-to-side duodenojejunostomy is a technically easier procedure, owing to wide stoma and sparing of mesenteric side. [ 12 ] Lastly, it was left to determine the oncological adequacy in terms of short- and long-term survival, recurrence and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that duodenal infiltration does not serve as a sign of unresectability or a reason to undergo HPD. For the majority of these patients, a distal gastrectomy combined with resection of the first segment of the duodenum, or a duodenal sleeve resection can accomplish an oncologically appropriate R0 resection[ 178 ].…”
Section: Studies On Surgical Approach and Resectionmentioning
confidence: 99%